Administrative Liability for Causing Damage to Selected Components of the Environment - Cepek, Branislav (Public Governance, Administration and Finances Law Review, 2020)
The article deals with one of the most important and recent issues of the contemporary law of the Member States and the EU in the field of environment, which is criminal liability for environmental crimes which serves as a tool for promoting environmental protection. Environmental law can be divided into two basic types of environmental liability for damage to the environment and liability for damage. Liability for environmental damage is divided into civil liability for damage as well as liability of the public for ecological damage. A special case is liability for historical damage. The Directive on torts is divided into criminal liability and administrative liability. In this paper, the author focuses on the analysis of the contemporary Czech tort law in the field of biodiversity protection and considers several aspects of this a de lege ferenda issue.